Rewards and intrinsic motivation : resolving the controversy - Cameron, Judy, 1953- (Bergin & Garvey, 2002)
Contrary to many claims, rewards do not have pervasive negative effects; instead, with careful arrangement of rewards, motivation, performance, and interest are enhanced. Over the past 30 years, many social psychologists have been critical of the practice of using incentive systems in business, education, and other applied settings. The concern is that money, high grades, prizes, and even praise may be effective in getting people to perform an activity but performance and interest are maintained only so long as the reward keeps coming. Once the reward is withdrawn, the concern is that individuals will enjoy the activity less, perform at a lower level, and spend less time on the task. The claim is that rewards destroy people's intrinsic motivation. Widely accepted, this view has been enormously influential and has led many employers, teachers, and other practitioners to question the use of rewards and incentive systems in applied settings. Contrary to this view, the research by Cameron and Pierce indicates that rewards can be used effectively to enhance interest and performance. The book centers around the debate on rewards and intrinsic motivation.; Based on historical, narrative, and meta-analytic reviews, Cameron and Pierce show that, contrary to many claims, rewards do not have pervasive negative effects. Instead, the authors show that careful arrangement of rewards enhances motivation, performance, and interest. The overall goal of the book is to draw together over 30 years of research on rewards, motivation, and performance and to provide practitioners with techniques for designing effective incentive systems.